Mengoptimalkan Efektivitas Komunikasi Bisnis Internal Dan Eksternal Untuk Peningkatan Kinerja Organisasi - Dian Mei Suri; Nurul Amelia Pratiwi Ritonga; Thalia Anandani; Suhairi Suhairi (Universitas Dian Nuswantoro, 2022)
Effective business communication is an important key in achieving strategic goals and has a role to improve organizational performance. This journal aims to analyze the importance of effective business communication, both internally and externally. This journal discusses the meaning of internal and external business communication, challenges in internal and external business communication that may be faced by organizations during the process of implementing effective business communication, the impact of ineffective business communication on the organization, this aims to increase awareness for the organization to understand how important effective business communication is, and the last is the recommended strategy to deal with challenges and obstacles that may occur during the process of implementing effective business communication.